A NEW RECORD OF GIANT LIZARD MANTIS OF LYSIOSQUILLA SULCIROSTRIS (KEMP, 1913) (FAMILY : LYSIOSQUILLIDAE) (GIESBRECHT, 1910) OFF THOOTHUKUDI COAST OF GULF OF MANNAR (08º 35’ 22.5" N lat. 78º 27’ 40.9" E long and 08º 31’ 91.2"N lat. 78º 25’ 32.7"E) - T. Vaitheeswaran (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The giant lizard mantis of Lysiosquilla sulcirostris Kemp, 1913 was recorded for the first time from Thoothukudi waters while investigating the biodiversity of the Gulf of Mannar during September, 2013. One specimen of the said species was collected as an incidental by-catch in the trawl fisheries off Thoothukudi coast of Gulf of Mannar, between 08º 35’ 22.5" N lat. 78º 27’ 40.9" E long and 08º 31’ 91.2"N lat. 78º 25’ 32.7"E long at a depth of 150-160 m.